Clothes-in-Process: Touch, Texture, Time. (3rd July 2019) - Stanes, Elyse
Abstract: Contemporary research on fashion consumption has largely focused on the surface qualities of dress, comprising questions of esthetics, expression, and identity. Rather than thinking about how clothes look, this paper considers how clothes feel . Theorizing clothes as always in-process rather than stable or static, this paper uses touch as lens to explore haptic and sensuous engagements that occur across a garments prosaic biography. Informed by five vignettes from a broader ethnographic project concerning clothes use, touch is located in conversations with hands and bodies. These conversations cultivate somatosensory relations with clothes that are "in-process", in various states of wear and repair, texture, and time. The material qualities of garments emerge as an active, tangible force that works alongside an evolving dialog of use—as clothes "wear in" or "wear out." This paper illustrates two ways in which touch informs clothes-in-process: how bodies come to know the fabric of clothes, and how the surface qualities of clothes push back against bodies of wearers. Although mundane and instinctive, the liveliness of materials and the haptic skills that attend to the use of clothes-in-process speak to value, care, and responsibility. But somatosensory relations also encompass discomfort and anxiety, leading to accumulations of clothes as matter out of place. Paying greater attention to the somatosensory registers of the body provides insights about the material meanings of clothes as garments wear over time. In light of the social and environmental implications of clothes and clothes use, such insights are important for advancing knowledge about how wearers interact with their clothes, over time.